2015
DOI: 10.3343/alm.2015.35.5.523
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Tedizolid Against Gram-Positive Bacteria in Patients With Skin and Skin Structure Infections and Hospital-Acquired Pneumonia: A Korean Multicenter Study

Abstract: We compared the activities of tedizolid to those of linezolid and other commonly used antimicrobial agents against gram-positive cocci recovered from patients with skin and skin structure infections (SSSIs) and hospital-acquired pneumonia (HAP) in Korean hospitals. Gram-positive isolates were collected from 356 patients with SSSIs and 144 patients with HAP at eight hospitals in Korea from 2011 to 2014. SSSIs included impetigo, cellulitis, erysipelas, furuncles, abscesses, and infected burns. Antimicrobial susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 13 publications
2
16
0
Order By: Relevance
“…Numerous in vitro surveys have demonstrated that tedizolid is 4-to 8-fold more potent than linezolid against species of staphylococci, enterococci, and streptococci, including those with multidrug-resistant (MDR) phenotypes, such as MRSA, VRE, and linezolid-resistant S. aureus and enterococci (3)(4)(5). Structural modifications in the molecule result in enhanced binding to the 23S rRNA target and provide enhanced activity of tedizolid compared to that of linezolid; furthermore, tedizolid potency is not affected by strains harboring the transmissible cfr resistance gene (1,2,6).…”
mentioning
confidence: 99%
“…Numerous in vitro surveys have demonstrated that tedizolid is 4-to 8-fold more potent than linezolid against species of staphylococci, enterococci, and streptococci, including those with multidrug-resistant (MDR) phenotypes, such as MRSA, VRE, and linezolid-resistant S. aureus and enterococci (3)(4)(5). Structural modifications in the molecule result in enhanced binding to the 23S rRNA target and provide enhanced activity of tedizolid compared to that of linezolid; furthermore, tedizolid potency is not affected by strains harboring the transmissible cfr resistance gene (1,2,6).…”
mentioning
confidence: 99%
“…strains, while linezolid’s MIC range was 0.5–2 mg/L 54. Tedizolid MIC 90 value was 0.5 mg/L against 873 enterococci included in other study while linezolid’s MIC 90 was 2 mg/L 56…”
Section: Review Of Microbiologymentioning
confidence: 82%
“…Tedizolid shows excellent activity against anaerobic Gram-positive microorganisms 54. Tedizolid’s MIC range against these microorganisms was four to eight times lower than that observed with linezolid.…”
Section: Review Of Microbiologymentioning
confidence: 87%
See 2 more Smart Citations